Enhanced Answer Generation from Web Information - Umesh S, Chaudhari; Shivaji B, Patil; Omprakash B, Bhange; Amin R, Abbas (International Journal of Computer Sciences and Engineering, 2015)
Nowadays Question answering services have gained very popular. It helps all members to post and answer questions as well enables general users to check information from a total set of well answered questions. But, existing QA applications mainly provides only textual answers, which are not enough understandable for many questions. In this paper, we are going to create a scheme that is able to provide textual answers in Question answering with particular media data. This approach get easily checks which type of media information should be added for answers. It then collects data from the web to enrich the answer. This web application type service contain three facts: answer medium selection, query generation for multimedia search, and multimedia data selection and presentation. To answer any query this system process a large set of QA pairs and add them to a pool, it can enable a novel multimedia question answering (MMQA) approach as users can find multimedia answers by matching their questions with those in the pool. There are many different QA research efforts that finds directly answer questions with multimedia data i.e. images and videos, but our approach is created based on community contributed textual question answers and thus it is helps to deal with more day to day needed community complex questions. We have conducted much performances on a multisource QA database’s. The results demonstrate the effectiveness of our approach.